Registral Streams, Fusion, and Prolongation in Åke Hermanson’s Alarme for Solo Horn, Op. 1 - Harper, Stephen (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2007)
Ake Hermanson’s Alarme, op. 11 for solo horn presents an interesting study piece for exploring harmonic prolongation in atonal music. As a piece without any simultaneities, the work requires all harmonies to be assembled by the listener. The motivic material itself facilitates this process in some ways, especially in those cases in which Hermanson employs an oscillation of two notes (usually some sort of iconic siren). Additionally, Hermanson’s limited intervallic palette (mostly intervals 2, 6, 11, and 13) creates distinct registral strands which can be followed as contrapuntal voices. This essay traces how registral streams contribute to harmonic formation and prolongation in this work.